Monitoring and Mitigating Particulate Matter Deposition on Decorative Surfaces: Current and Future Approaches in the Palace of Westminster. (1st August 2018) - Fox, Sarah-Jane; Babington, Caroline; Macalister, Fiona; Bower, Thomas; Martin de Fonjaudran, Charlotte
ABSTRACT: Research into dust deposition rates on the wall paintings in the State Apartments at the Palace of Westminster, London, UK, began during the restoration of the encaustic floor tiles. The study has broadened to inform day-to-day preventive care for the extensive fine art collections on display and the intricately decorated Gothic interiors, providing a powerful tool for the forthcoming restoration and renewal of the Palace. Different monitoring methods, using optical microscopy, macro-photography and software-based image analysis, were investigated. Qualitative analysis with SEM-EDX and optical microscopy allowed the identification of a number of anthropogenic, geogenic and biological sources of particulate matter, while quantitative results elucidated deposition trends, highlighting both seasonal and works-related impacts. Results indicated that mitigation measures taken to protect works of art and limit the diffusion and deposition of particulate matter on surrounding surfaces were successful. A new dust monitoring method, based on imaging of vertical surfaces and on a recently developed image analysis workflow (CHIJ) operated in open-source software (ImageJ) was trialled alongside more traditional methods for measuring dust deposition through collection of particulate matter on proxies. Results showed significant discrepancies between data acquired directly on wall painting surfaces as compared to horizontal glass slides. The advantages, limitations and complementarity of both monitoring methods were identified, and their potential contributions to the development of data-driven conservation approaches for heritage sites were assessed. The relatively low-tech methods and equipment used present useful and adapted tools for collection managers and conservators to inform their decision-making processes.